2012
DOI: 10.1109/tmech.2011.2131673
|View full text |Cite
|
Sign up to set email alerts
|

Study of Forces During Microassembly Tasks Using Two-Sensing-Fingers Grippers

Abstract: In this paper, the use of a two-sensing-fingers gripper for grasping planar microparts (smaller than 0.1 mm 3 ) is being investigated and the force range during a micro-assembly sequence is estimated between 0 to 3 mN. An analytical model of their gripping forces in the presence of a lateral contact force is proposed and it is compared to FEA (Finite Element Analysis). An experimental validation is performed by a proposed setup for a lateral contact force in the range of a few tens to hundreds of µN. Effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…In literature, the most used solution is to use a microgripper with an active finger and a force sensing finger. However, in previous works [9], the use of two-sensing-fingers microgripper provides an estimation of the lateral contact force between the manipulated micropart and the microassembly substrate in addition to the gripping forces.…”
Section: Microgripper With Sensorized End-effectorsmentioning
confidence: 99%
“…In literature, the most used solution is to use a microgripper with an active finger and a force sensing finger. However, in previous works [9], the use of two-sensing-fingers microgripper provides an estimation of the lateral contact force between the manipulated micropart and the microassembly substrate in addition to the gripping forces.…”
Section: Microgripper With Sensorized End-effectorsmentioning
confidence: 99%
“…As compared with conventional 1-DOF gripping, the 2-DOF positioning allows a more dexterous manipulation for practical applications. In the future work, a prototype of the designed microgripper will be fabricated and a simultaneous position/force control [22], [23] will be conducted through experimental investigations.…”
Section: Analytical Computation and Fea Simulationmentioning
confidence: 99%
“…It was shown that the evolution of the gripping forces follows two steps, according to the contact between the microgripper fingers and the rigid micropart: planar contact and edge/vertex contact [21]. The planar contact is characterized by the linear displacement of the micropart and the edge/vertex contact by the combined linear translational displacement of the micropart along Y for small F y force and rotation around X for higher F y .…”
Section: ) Stability According To a F Z Perturbation (Fig 5)mentioning
confidence: 99%
“…In these works, AFM probes are often used or grippers with one sensing fingers and one actuated finger. The use of two-sensing-finger allows to detect the side of contact [21] and to control the gripping forces at the same time or independently (picking of a micropart). Such a system brings suitable information about the contact, provides more dexterity of the grasp and ensures more safety to not break microparts.…”
Section: Introductionmentioning
confidence: 99%